Analysis of the Artistic and Cultural Characteristics of White Tibetan House in Xiangcheng County from the Perspective of Symbolism - Zhang, Ziqi (Journal of Education and Educational Technologies, 2023)
As a cultural carrier, residential buildings can not only meet people 's material needs, but also convey the spirit. Symbolism is the soul of architecture. It conveys the good wishes and spiritual pursuit of human beings through architectural ontology, and has rich artistic and cultural characteristics. As a unique Tibetan architecture, the White Tibetan House, together with temples and crazy costumes, is known as the " three absolutes of the countryside and the city ' and is a symbolic symbol of the regional culture of the countryside and the city. Through the study of the white Tibetan houses in Xiangcheng County, this paper analyzes the symbolism contained in the three levels of ' shape symbol', 'object symbol' and 'color symbol' from the aspects of its overall structure, decorative details and color application, and further shows the rich plastic arts and profound national culture of the white Tibetan houses in Xiangcheng County.